ANALISIS YIELD SPREAD OBLIGASI BERDASARKAN FAKTOR DEFAULT DAN FAKTOR NON-DEFAULT : STUDI EMPIRIK PADA OBLIGASI KORPORASI DI SEKTOR KEUANGAN - Anita Giovanni; Siti Saadah (Prosiding Working Papers Series In Management, 2018)
Bond is a financial assets investment instrument in capital market that is relatively new when compared to stock. In Indonesia, the research related to bonds, especially yield spread is very limited, thus it encourages author to analyze yield spread behavior based on several predictors such as SBI rate, bonds rating, return on equity (ROE), debt to equity ratio (DER) and macaulay duration. Multiple linear analysis method which is applicated to cross section data in this research shows that bonds rating and macaulay duration have a significant effect to yield spread on corporate bonds in financial sectors, in other words, investors consider bond rating and duration before agreeing bonds indenture. SBI rate, in the opposite, shows no significant effect on yield spread. This result may happen because of time lag in the transmission monetary policy mechanism process. Financial ratio such as return on equity and debt to equity ratio also show no significant effect on yield spread. It is possibly caused by the default risks of those financial ratio have already reflected on bonds rating, so investors do not consider ROE and DER directly.Keywords: Yield Spread, Bonds, Default, Non-Default